"Family Support Would Have Been Like Amazing": LGBTQ Youth Experiences With Parental and Family Support. (January 2017) - Roe, Stuart
This qualitative study examines gay and bisexual adolescent experiences with parental and family support using a phenomenological inquiry approach. Four themes related to peer support emerged from the data including (1) coming out was necessary; (2) initial reactions of parents are most often not positive; (3) lesbian, gay, bisexual, transgender, and questioning (LGBTQ) youth view religion as a barrier to support from parents; and (4) LGBTQ youth want explicit support from parents and family members. Implications for counselors working with parents, families, and individuals are discussed.